5v+7=6v-11

Simple and best practice solution for 5v+7=6v-11 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5v+7=6v-11 equation:


Simplifying
5v + 7 = 6v + -11

Reorder the terms:
7 + 5v = 6v + -11

Reorder the terms:
7 + 5v = -11 + 6v

Solving
7 + 5v = -11 + 6v

Solving for variable 'v'.

Move all terms containing v to the left, all other terms to the right.

Add '-6v' to each side of the equation.
7 + 5v + -6v = -11 + 6v + -6v

Combine like terms: 5v + -6v = -1v
7 + -1v = -11 + 6v + -6v

Combine like terms: 6v + -6v = 0
7 + -1v = -11 + 0
7 + -1v = -11

Add '-7' to each side of the equation.
7 + -7 + -1v = -11 + -7

Combine like terms: 7 + -7 = 0
0 + -1v = -11 + -7
-1v = -11 + -7

Combine like terms: -11 + -7 = -18
-1v = -18

Divide each side by '-1'.
v = 18

Simplifying
v = 18

See similar equations:

| 6x=5x+16 | | 16(x+3)-4x=4(3x+2)-12 | | 5(3x-7)-(3x+9)= | | 19-u=238 | | -8(b-5)=-2(b+1) | | a-3[b-2(c-x)]=4 | | 167=2(3w-5)+2w | | 3x+6=9(x+4) | | 3(6p+5)=21 | | 3x+6=9(x+9) | | 7(4x+7)=6(1+x)-1 | | 2e^3x-2=7 | | C-13=5(3) | | 40=8(n-2) | | -5(8x+4)=-140 | | c=49.99-.25*49.99 | | 4[8-(-9x-1)]=180x+52 | | 3y-10x=-45 | | 5(4x-3)=15 | | x=(4y-9)(6y-7) | | 5+x=4(8) | | y+8=3(x+15) | | 70619.542=2*3.14*1303.21+2*3.14*36.1*h | | 2+4sinx=0 | | 422.67=c+.15c | | -(-4x+10-8y)= | | 8+3m-4=6m+9-2m | | 4x-5+x=7+5x-2 | | y+8=3(x+5) | | 3n-2(n+10)=n-20 | | 2w+6x-14y+8w+9x+6y= | | 81650.99=2*3.14*r^2+2*3.14*287.8*r |

Equations solver categories